2013
DOI: 10.1158/1541-7786.mcr-12-0527
|View full text |Cite
|
Sign up to set email alerts
|

MnSOD Promotes Tumor Invasion via Upregulation of FoxM1–MMP2 Axis and Related with Poor Survival and Relapse in Lung Adenocarcinomas

Abstract: Manganese superoxide dismutase (MnSOD) is an antioxidant enzyme responsible for the elimination of superoxide radical. The role of MnSOD in tumor progression in different human cancers is still controversial. In the present study, MnSOD expression in lung cancer cells was explored by knockdown or overexpression using transfection of a short hairpin RNA (shRNA) or an expression vector, respectively, to determine whether MnSOD expression mediates lung cancer cell migration, invasion, and oncogenic potential by i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 37 publications
5
43
0
Order By: Relevance
“…Previous studies reported roles for MMP2 in regulating lung cancer invasion and vascular permeability . In the present study, exogenous overexpression and interference experiments showed that lnc‐MMP2‐2 promoted lung cancer invasion and increased vascular permeability, and that lnc‐MMP2‐2 expression was markedly higher in lung cancer tissues than in normal controls.…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies reported roles for MMP2 in regulating lung cancer invasion and vascular permeability . In the present study, exogenous overexpression and interference experiments showed that lnc‐MMP2‐2 promoted lung cancer invasion and increased vascular permeability, and that lnc‐MMP2‐2 expression was markedly higher in lung cancer tissues than in normal controls.…”
Section: Discussionsupporting
confidence: 60%
“…MnSOD was shown promoting breast cancer metastasis and anoikis resistance, 47 as well as enhancing lung cancer cell invasion through upregulating FoxM1 and MMP2 expression. 48 On the other hand, overexpression of MnSOD was shown to inhibit cell proliferation or suppress malignant phenotype of pancreatic cancer cells, 49, 50 breast cancer cells 51 and prostate cancer cells. 51, 52 Furthermore, oncolytic adenovirus carrying gene encoding MnSOD was shown to significantly suppress colon cancer cell growth both in vitro and in vivo through activating the Bax–cytochrome c –caspase-9–caspase-3 apoptotic signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…8, 9 The eGFP-FOXM1 and pcDNA3-FOXM1 WT and 5x(K>R) mutant expression plasmids have also been described. 15 The expression vectors for RNF8, 25 RNF168, 30 Flag-RNF168 31 and HA-RNF8 32 have also been described previously. The pcDNA3-RNF4 plasmid was from Prof Ron T. Hay (University of Dundee, Dundee, UK).…”
Section: Methodsmentioning
confidence: 99%